A critique of the role of NGOs as partners in governance. Issue 1 (2nd January 2020) - Haque, M. Shamsul
Abstract : In the current age, with the diminishing role of the state, there is a growing significance of its partnership with non-state actors, including private enterprises, local authorities and non-government organisations (NGOs). In particular, there is greater recognition in the developing world of the state's partnership with NGOs in delivering goods and services, especially in line with the new framework of shared governance prescribed by international agencies and donors. Despite the overwhelmingly favourable views on such partnership disseminated worldwide by its advocates, many critics draw attention to its adverse consequences such as the use of NGOs as profit-making ventures, avoidance of government's social responsibilities by transferring them to NGOs, and ineffectiveness of government's public accountability. Questions can also be raised regarding the reliability and legitimacy of NGOs as partners. As most studies on NGO partnership tend to overlook these concerns, this article offers a critique of the state's partnership with NGOs in the case of Bangladesh where there are some of the world's largest and most widely recognised NGOs. These concerns related to the partnership of NGOs in governance can also be observed in other developing nations.